2009
DOI: 10.1073/pnas.0900089106
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated gene expression networks in human acute myelogenous leukemia stem cells

Abstract: We performed the first genome-wide expression analysis directly comparing the expression profile of highly enriched normal human hematopoietic stem cells (HSC) and leukemic stem cells (LSC) from patients with acute myeloid leukemia (AML). Comparing the expression signature of normal HSC to that of LSC, we identified 3,005 differentially expressed genes. Using 2 independent analyses, we identified multiple pathways that are aberrantly regulated in leukemic stem cells compared with normal HSC. Several pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
246
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 253 publications
(259 citation statements)
references
References 40 publications
10
246
0
1
Order By: Relevance
“…29 A similar observation was made by Gerber et al 30 for hTERT, proteinase 3 and survivin, which were shown to be downregulated in chronic myeloid leukemia (CML)-LSCs relative to normal HSCs. 30 Interestingly, in this study, conversion of chronic phase CML to blast crisis-which resembles AML-was paralleled by a further decrease in hTERT, proteinase 3 and survivin expression levels in the LSC compartment.…”
Section: Criterion 2: Frequency and Pattern Of Expressionsupporting
confidence: 62%
See 4 more Smart Citations
“…29 A similar observation was made by Gerber et al 30 for hTERT, proteinase 3 and survivin, which were shown to be downregulated in chronic myeloid leukemia (CML)-LSCs relative to normal HSCs. 30 Interestingly, in this study, conversion of chronic phase CML to blast crisis-which resembles AML-was paralleled by a further decrease in hTERT, proteinase 3 and survivin expression levels in the LSC compartment.…”
Section: Criterion 2: Frequency and Pattern Of Expressionsupporting
confidence: 62%
“…28 This explains the impetus behind latest efforts to better characterize LSCs and to unravel their gene expression profiles. Majeti et al 29 compared the gene expression signature of LSCs with that of normal HSCs and identified over 3000 genes with dysregulated expression in LSCs. 29 The published data set also includes several genes encoding proteins that can be recognized by the immune system and act as LAAs, such as Elicited (T) 47,95 Natural (B/T) 25 …”
Section: Criterion 2: Frequency and Pattern Of Expressionmentioning
confidence: 99%
See 3 more Smart Citations